Tantangan Strategi Kreatif Pembelajaran Teori Kognitif dalam Meningkatkan Minat Belajar Matematika Siswa Kelas 5 Sekolah Dasar - Oktawiryati, Ni Putu; Suarni, Ni Ketut; Margunayasa, I Gede (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study was conducted in response to the observed obstacle, namely the lack of interest in learning mathematics in grade 5 elementary school students. This research reveals challenges in increasing interest in learning mathematics for grade 5 elementary school students through the application of Creative Strategies for Learning Cognitive Theory. These challenges arise from the low interest in learning mathematics at the elementary level and the need for innovative learning approaches. This study is an experimental study with a focus on the subject of grade 5 students as a population. The data collection method is done through observation, interviews, and tests. Data analysis uses qualitative and quantitative approaches to illustrate the impact of creative strategies in increasing interest in learning mathematics. The results revealed significant differences in students' mathematical learning interest engaged in creative strategies of cognitive theory learning compared to the control group.